Competition among native and invasive Phragmites australis populations: An experimental test of the effects of invasion status, genome size, and ploidy level. Issue 3 (13th January 2020) - Pyšek, Petr; Čuda, Jan; Šmilauer, Petr; Skálová, Hana; Chumová, Zuzana; Lambertini, Carla; Lučanová, Magdalena; Ryšavá, Hana; Trávníček, Pavel; Šemberová, Kristýna; Meyerson, Laura A.
Abstract: Among the traits whose relevance for plant invasions has recently been suggested are genome size (the amount of nuclear DNA) and ploidy level. So far, research on the role of genome size in invasiveness has been mostly based on indirect evidence by comparing species with different genome sizes, but how karyological traits influence competition at the intraspecific level remains unknown. We addressed these questions in a common‐garden experiment evaluating the outcome of direct intraspecific competition among 20 populations of Phragmites australis, represented by clones collected in North America and Europe, and differing in their status (native and invasive), genome size (small and large), and ploidy levels (tetraploid, hexaploid, or octoploid). Each clone was planted in competition with one of the others in all possible combinations with three replicates in 45‐L pots. Upon harvest, the identity of 21 shoots sampled per pot was revealed by flow cytometry and DNA analysis. Differences in performance were examined using relative proportions of shoots of each clone, ratios of their aboveground biomass, and relative yield total (RYT). The performance of the clones in competition primarily depended on the clone status (native vs. invasive). Measured in terms of shoot number or aboveground biomass, the strongest signal observed was that North American native clones always lost in competition to the other two groups. In addition, North American native clones were suppressed by European natives to a similar degree as by North American invasives. North American invasive clones had the largest average shoot biomass, but only by a limited, nonsignificant difference due to genome size. There was no effect of ploidy on competition. Since the North American invaders of European origin are able to outcompete the native North American clones, we suggest that their high competitiveness acts as an important driver in the early stages of their invasion. Abstract : We address experimentally, for the first time, competition between three phylogeographic groups of Phragmites australis, a globally important species providing ecosystem services in wetlands—we explored competition between native North American populations, invasive populations in North America that were introduced from Europe, and their native European counterparts from which they originated. Based on our previous studies on the role that genome size plays in this particular invasion, we tested the effect of karyological characteristics (genome size and ploidy levels) of competing population on the outcome of competition.